Arrest and Detention in Indonesian Criminal Procedure Code under Human Rights Perspective - Muhammad Arif Setiawan (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2022)
This paper aims to analyze the regulatory framework on arrest and detention in Indonesian Criminal Procedure Code under human rights perspective. This study employed doctrinal legal research using statute and conceptual approaches. The findings of this research reveal that the principles of law enforcement and human rights, which include the principles of legality, necessity, and proportionality, are essentially general principles that can be used to determine whether state actions that interfere with citizens' rights and freedoms violate or do not violate human rights. The legal provisions concerning arrest and detention did not fit the human rights standpoint particularly in the context of procedure and the length of detention. The proportionality and the necessity principle have not been fully considered as the ethical basis for arresting the perpetrator of a crime. Hence, what is needed is to amend the Criminal Procedure Code considering the adoption of both necessity and proportionality principle in the arrest and detention.